ANTIISCHEMIC METABOLIC MODULATOR TRIMETAZIDINE IN TREATMENT OF CORONARY HEART DISEASE - V. P. Lupanov (Российский кардиологический журнал)
Meta-analytic data shows that addition of trimetazidine (TMZ) to standard therapy increases significantly exercise tolerance in ischemic heart disease (IHD) patients. In heart failure due to IHD, condition improves as well, administering TMZ. There is no strict evidence that TMZ is especially effective in people with comorbid diabetes. TMZ shows significant antianginal effect in combination with other medications that is, certainly, improves life quality of patients.